APLIKASI SISTEM PAKAR UNTUK IDENTIFIKASI PADA PENYAKIT TELINGA, HIDUNG DAN TENGGOROKAN (THT) MENGGUNAKAN METODE FORWARD CHAINING - Eka Satriyawati; Muhammad Ridwan Effendi (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2021)
AbstractEar, nose and throat (ENT) disease is one type of disease that is often found in the community. The number of complaints and symptoms that exist and various types of ENT diseases make identification of ENT diseases difficult. The expert system design method to identify the type of diabetes mellitus is using the System Development Life Cycle (SDLC) method. System Development Life Cycle is the stages of work carried out by systems analysts and programmers in building systems. The system design method used is the Waterfall Model. The application of the Forward Chaining method is a search technique that starts with known facts with known facts, then matches these facts with the IF part of the IF-THEN rule. If there are facts that match the IF part, then the rule is executed. When a rule is executed a new fact (the THEN section) is added to the database. Each time a match, starting from the top rule. Each rule can only be executed once. The matching process stops when there are no more executable rues. The results and targets of the research are in the form of an Expert System mobile-based application in diagnosing ear, nose, and throat diseases using the forward chaining method.Â Keywords: Expert System, Forward Chaining, Ear Nose Throat Disease